2010
DOI: 10.1167/10.8.17
|View full text |Cite
|
Sign up to set email alerts
|

Detectability of sine- versus square-wave disparity gratings: A challenge for current models of depth perception

Abstract: Stereo vision is an area in which we are increasingly able to construct detailed numerical models of the computations carried out by cerebral cortex. Piecewise-frontoparallel cross-correlation is one such model, closely based on the known physiology and able to explain important aspects of human stereo depth perception. Here, we show that it predicts important differences in the ability to detect disparity gratings with square-wave vs. sine-wave profiles. In particular, the model can detect square-wave grating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
37
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(40 citation statements)
references
References 42 publications
2
37
1
Order By: Relevance
“…Interestingly, 2 of our 4 human observers also displayed this tendency (Figure 10 of [10]), while neither humans nor model ever displayed an earlier drop for square-waves than for sine-waves.…”
Section: Resultsmentioning
confidence: 71%
See 1 more Smart Citation
“…Interestingly, 2 of our 4 human observers also displayed this tendency (Figure 10 of [10]), while neither humans nor model ever displayed an earlier drop for square-waves than for sine-waves.…”
Section: Resultsmentioning
confidence: 71%
“…We therefore tested human observers on dense random-dot stereograms depicting square-wave gratings. We found that the model's prediction was not borne out: humans never showed significantly better ability to detect square-wave than sine-wave gratings [10]. Figure 2 shows example human and model data near the upper frequency limit, illustrating the marked qualitative difference between the model and the human observers.…”
Section: Introductionmentioning
confidence: 93%
“…More recently, however, similarity-based matching has been implicit in models that measure disparity using cross-correlation (Banks et al, 2004; Filippini and Banks, 2009; Allenmark and Read, 2010, 2011) or cross-correlation-like (Fleet et al, 1996; Qian and Zhu, 1997; Chen and Qian, 2004) procedures. Such models encode similarity by cross-correlating spatially extended image patches.…”
Section: Introductionmentioning
confidence: 99%
“…Our formulation of the relationship between disparity threshold and image contrasts in the two eyes is based on the cross-correlation model, which has received support from many psychophysical experiments (Allenmark & Read, 2010Banks, Gepshtein, & Landy, 2004;Cormack et al, 1991;Filippini & Banks, 2009;Harris, McKee, & Smallman, 1997;Nienborg, Bridge, Parker, & Cumming, 2004), and has found many successful applications in computer vision (Clerc & Mallat, 2002;Donate, Liu, & Collins, 2011;Heo, Lee, & Lee, 2011;Kanade & Okutomi, 1994). The product rule in the cross-correlation model is consistent with the prevailing disparity energy models of V1 neurons (Anzai et al, 1999a(Anzai et al, , 1999bChen & Qian, 2004;Filippini & Banks, 2009;Ohzawa, 1998;Ohzawa, DeAngelis, & Freeman, 1990Qian, 1994Qian, , 1997 when the outputs of binocular complex cells with opposite preferred polarities of disparity are compared to extract the polarity of the perceived disparity.…”
Section: Elaboration Of the MCM To Model Stereo Depth Perceptionmentioning
confidence: 99%